An orthotropic interface damage model for simulating drying processes in soils - Manzoli, Osvaldo [UNESP]; Sánchez, Marcelo; Maedo, Michael; Hajjat, Jumanah; Guimarães, Leonardo J. N. (Springer Nature, 2018)
The study of drying process in soils has received an increased attention in the last few years. This is very complex phenomenon that generally leads to the formation and propagation of desiccation cracks in the soil mass. In recent engineering applications, high aspect ratio elements have proved to be well suited to tackle this type of problem using finite elements. However, the modeling of interfaces between materials with orthotropic properties that generally exist in this type of problem using standard (isotropic) constitutive model is very complex and challenging in terms of the mesh generation, leading to very fine meshes that are intensive CPU demanding. A novel orthotropic interface mechanical model based on damage mechanics and capable of dealing with interfaces between materials in which the strength depends on the direction of analysis is proposed in this paper. The complete mathematical formulation is presented together with the algorithm suggested for its numerical implementation. Some simple yet challenging synthetic benchmarks are analyzed to explore the model capabilities. Laboratory tests using different textures at the contact surface between materials were conducted to evaluate the strengths of the interface in different directions. These experiments were then used to validate the proposed model. Finally, the approach is applied to simulate an actual desiccation test involving an orthotropic contact surface. In all the application cases the performance of the model was very satisfactory.
Keywords: Drying cracks; Mesh fragmentation; Orthotropic interphase elements; Orthotropic shear strength; Shrinkage 3D FE modeling